2002
DOI: 10.3168/jds.s0022-0302(02)74155-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Phenotypic Relationships Among Endocrine and Traditional Fertility Traits and Production Traits in Holstein-Friesian Dairy Cows

Abstract: The objective of this study was to estimate the heritability of a number of traditional and endocrine fertility traits in addition to d-56 predicted milk yield (MY56), and the genetic and phenotypic correlations between these traits. Various fixed effects such as season, year, herd, lactation number, diet, percentage Holstein (PCH) of the cow, and occurrence of uterine infection (UI), dystocia (DYS), and retained placenta (RP) were also investigated. Data collected for 1212 lactations of 1080 postpartum (PP) H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
132
2
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(158 citation statements)
references
References 35 publications
22
132
2
1
Order By: Relevance
“…The heritability estimates of CFH and CFS, however, are slightly larger than that generally observed from field data, which may be attributable to an expected greater accuracy of recording in experimental herds. The heritability estimate for CLA in the present study (0.13) is slightly lower than estimates of 0.16 reported elsewhere (Veerkamp et al, 2000;Royal et al, 2002;Petersson et al, 2007), although some degree of similarity is expected as the data used in the present study was also included in some previous estimates (Veerkamp et al, 2000). The phenotypic correlations among the different fertility traits are in general agreement with previous studies.…”
Section: Genetic Parameterssupporting
confidence: 85%
See 4 more Smart Citations
“…The heritability estimates of CFH and CFS, however, are slightly larger than that generally observed from field data, which may be attributable to an expected greater accuracy of recording in experimental herds. The heritability estimate for CLA in the present study (0.13) is slightly lower than estimates of 0.16 reported elsewhere (Veerkamp et al, 2000;Royal et al, 2002;Petersson et al, 2007), although some degree of similarity is expected as the data used in the present study was also included in some previous estimates (Veerkamp et al, 2000). The phenotypic correlations among the different fertility traits are in general agreement with previous studies.…”
Section: Genetic Parameterssupporting
confidence: 85%
“…The use of hormonal profiles, related to fertility performance, can aid in Figure 2 Posterior quantitative trait locus probabilities, from top to bottom, for calving interval, number of services and pregnancy rate to first service for each of the autosomes from left (BTA 1) to right (BTA 29) and the X-chromosome at the far right. circumventing some of the limitations of traditional measures, and previous research has shown that heritability estimates for fertility traits derived from progesterone profiles tend to be greater than traditional measures of fertility (Veerkamp et al, 2000;Royal et al, 2002;Petersson et al, 2007). Nonetheless, the quantity of data on progesterone profiles at an individual animal level is limited mainly because of the expense of collecting these data.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations